Bukti Asymetric Information dalam Kaitannya dengan Karakteristik Perusahaan yang Dimediasi oleh Disclosure : Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI - Handayani, Sri (Lembaga Penerbitan Unversitas Esa Unggul, 2013)
AbstractExtensive disclosure of financial statements is closely related to a mechanism to reduce the asymmetry information in order to reduce conflicts of interest arising from the separation of ownership with management. When confronted with the differences between investors and management information or information asymmetry, then it will certainly have an impact on the relevance of the information. The purpose of this study is to analyze the impact of corporate characteristics on information asymmetry to that mediated by the broad disclosure. This research was conducted at the company's manufacturing companies listed on the Stock Exchange in 2008-2010. The sampling method used was purposive sampling method, with consistent criteria manufacturing companies listed on the Stock Exchange in the year 2008-2010 and active stock trading. The type of data is secondary data sourced from the annual financial statements. Methods of data analysis using path analysis with OLS 2S. The results found that that the size of the Company, Firm Size and Profitability no effect Broad Disclosure. While LnLeverage and public ownership Ln significant effect on Broad Disclosure. Disclosure does not mediate the vast influence LnLeverage Company Size Size Firm Profitability on Information Asymmetry. Disclosure mediate LnKepemilikanSaham broad influence on Information Asymmetry.The conclusion from this study is that the company will be owned by the public limelight, so companies are trying to meet the public's desire to do as much as possible so that the disclosure will reduce information asymmetry.Keywords: disclosure, company size, leverage